Infrastructural Financing and Trade Performance in West Africa - (:unkn) unknown (My University, 2023)
This study examines the relationship between infrastructure and trade performance in West African countries during the 1990-2021. It moved a step further over the existing studies in this area to explore the effect of education and energy finance on trade flow in the region. The theoretical framework is based on the love of variety theory as advocated by Krugman [1] and modified to suit purpose. This emphasis here is on derivation of utility from a given varieties of choices which in turn boost production, specialization, positively externalities and economies of scale. Results of the robust least square show the declining effects of mobile phone subscriptions and increasing effect of government expenditure on education though not as expected. Investment in energy appears insufficient to boost trade performance in the region. The Wald test shows that causality occurs between import trade and infrastructure financing variables.
Keywords: African Research